Value Merchants Demonstrating and Documenting Superior Value in Business Markets. - Anderson, James C.; Kumar, Nirmalya; Narus, James A. (La Vergne : Harvard Business Review Press, 2007)
Do your salespeople feel under extreme pressure to retain accounts or gain new business at any cost' If so, you may be leaving big money on the table. Consider the integrated-circuit supplier representative who lost $500,000 of potential profit on a single transaction, just to "win" a deal that he would have closed anyway at the higher price. Do not make price concessions. Become a value merchant instead. In this authoritative book, James Anderson, Nirmalya Kumar, and James Narus explain how companies in business markets can use customer value management techniques to estimate the value of your market offerings, create value propositions that resonate with your customers, and maximize the return you will get on the superior value that you deliver. Drawing on extensive research and detailed case studies of companies like Sonoco, Tata Steel, and Quaker Chemical, Value Merchants will change the mindset and behavior of your executives, sales management, representatives, and marketers,as well as your customers.
Intro -- Contents -- Preface -- Acknowledgments -- Ch. 1: Value Merchants -- Ch. 2: Conceptualize Value -- Ch. 3: Formulate Value Proposition -- Ch. 4: Substantiate Value Propositions -- Ch. 5: Tailor Market Offerings -- Ch. 6: Transform the Sales Force into Value Merchants -- Ch. 7: Profit from Value Provided -- Ch. 8: Prosper in Business Markets -- Appendix A: Relating Customer Value and Price -- Appendix B: PeopleFlo EnviroGear Pump Customer Value Model -- Notes -- Index -- About the Authors
Description based upon print version of record.
Added to collection customer.56279.3
Keywords: Business; BUSINESS & ECONOMICS / Marketing / Industrial; Business; elektronické knihy; electronic books